Rapidly sintered cathode having optimal size and concentration of secondary phase and method for forming the same

KR103044159B1Active Publication Date: 2026-11-05CORNING INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
KR1020227037476
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-02
Filing Date
2021-03-26
Publication Date
2026-11-05
Estimated Expiration
2041-03-26

Smart Images

  • Figure 112022113264904-PCT00001_ABST
    Figure 112022113264904-PCT00001_ABST
Patent Text Reader

Abstract

A sintered electrode for a battery, wherein the sintered electrode has a first surface positioned toward a current collector and a second surface positioned toward an electrolyte layer, wherein the sintered electrode comprises: a first phase and a second phase, wherein: the first phase has a lithium compound, and the second phase has at least one of a porous structure or a solid-state Li-ion conductor, and the thickness of the sintered electrode between the first surface and the second surface is in the range of 10 μm to 200 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field This application claims priority to U.S. provisional patent application No. 63 / 004,136 filed on April 2, 2020, the entire contents of which are incorporated herein by reference. The present disclosure relates to a rapidly sintered cathode having an optimal size and concentration of a secondary phase. Background Technology Efforts to increase the energy density of lithium-ion (Li-ion) batteries are being pursued using solid-state (SS) battery structures with lithium (Li) metal anodes. The theoretical charge capacity of Li metal is about 10 times greater than that of graphite carbon used in conventional Li-ion batteries. Current efforts to develop SS Li-batteries have focused on developing materials with high Li-ion conductivity to minimize internal cell resistance for rapid charging and discharging. The slow Li-ion conduction in current cathode materials limits usable capacity, restricts charging speed and the ability to deliver continuous power, and makes the manufacturing of batteries with absolute capacity targets cumbersome and costly. The problem to be solved The present application discloses an improved cathode for Li-ion battery applications and a method for forming the same. means of solving the problem In some embodiments, as a sintered electrode for a battery, the sintered electrode has a first surface positioned toward a current collector and a second surface positioned toward an electrolyte layer, wherein the sintered electrode comprises: a first phase and a second phase, wherein: the first phase comprises a lithium compound, and the second phase comprises at least one of a porous structure or a solid-state Li-ion conductor, wherein: the thickness of the sintered electrode between the first surface and the second surface is in the range of 10 μm to 200 μm. In one aspect that can be combined with any other aspect or embodiment, the second phase comprises a porous structure, wherein: the sintered electrode comprises an open porosity in the range of 5% to 35%, and the porous structure is continuous within the first phase. In one aspect that can be combined with any other aspect or embodiment, the pores of the porous structure are aligned within an average of 25° from the vertical with respect to the first and second surfaces of the electrode to be sintered. In one aspect that can be combined with any of the other aspects or embodiments, the porous structure is infiltrated with a liquid electrolyte. In one aspect that can be combined with any of the other aspects or embodiments, the liquid electrolyte comprises at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bisoxalto borate (LiBOB), lithium difluorooxalto borate (LiDFOB), lithium trifluorosulfonylimide (LiTFSI), or a combination thereof. In one aspect that can be combined with any of the other aspects or embodiments, the second phase comprises a solid-state Li-ion conductor present in a range of 5 volume% to 35 volume% of the sintered electrode. In one aspect that can be combined with any of the other aspects or embodiments, a solid-state Li-ion conductor is 10 -4 It has a lithium ion conductivity exceeding S / cm. In one aspect that can be combined with any of the other aspects or embodiments, a solid-state Li-ion conductor is: lithium garnet (LLZO), lithium borate (LBO), lithium lanthanum titanate (LTO), lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), Li 11 AlP2S 12 , lithium phosphosulfide (LPS), a combination thereof, or at least one of doped variations thereof. In one aspect that can be combined with any of the other aspects or embodiments, the lithium compound comprises at least one of lithium cobaltite (LCO), lithium nickel manganese cobaltite (NMC), lithium manganite spinel, lithium nickel cobalt aluminate (NCA), lithium iron manganite (LMO), lithium iron phosphate (LFP), lithium cobalt phosphate, lithium nickel manganate, lithium titanium sulfide, or a combination thereof. In one aspect that can be combined with any of the other aspects or embodiments, the sintered electrode is a self-supporting substrate of the battery. In one aspect that can be combined with any other aspect or embodiment, the battery does not include an inactive substrate. In one aspect that can be combined with any of the other aspects or embodiments, the perimeter-to-surface area ratio between the first phase and the second phase is at least 0.4 μm -1 am. In one aspect that can be combined with any other aspect or embodiment, the cross-sectional area of ​​the sintered electrode is at least 3 cm². In some embodiments, the cathode for the battery comprises: a first phase and a second phase; and a first surface and a second surface, wherein the thickness between the first surface and the second surface is 10 μm to 200 μm; and wherein the cathode comprises: an open porosity in the range of 5% to 35%; 10 -4 Lithium ion conductivity exceeding S / cm; and at least 0.4 μm -1 It has at least one of the perimeter-to-surface area ratio between the first phase and the second phase. In one aspect that can be combined with any other aspect or embodiment, the cross-sectional area of ​​the sintered cathode is at least 3 cm². In one aspect that can be combined with any of the other aspects or embodiments, the battery comprises: a cathode of any embodiment described herein; an electrolyte material penetrating a porous region of said cathode; wherein the cathode is a substrate of the battery. In one aspect that can be combined with any of the other aspects or embodiments, the electrolyte is: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bisoxalto borate (LiBOB), lithium difluorooxalto borate (LiDFOB), lithium trifluorosulfonylimide (LiTFSI), or a combination thereof; lithium garnet (LLZO), lithium borate (LBO), lithium lanthanum titanate (LTO), lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), Li 11 AlP2S 12 It is selected from lithium phosphosulfide (LPS), combinations thereof, or doped variations thereof. In one aspect that can be combined with any other aspect or embodiment, the battery does not include an inactive substrate. In one aspect that can be combined with any other aspect or embodiment, the volume of the battery is smaller than the volume of the battery including the cathode disposed on an inert substrate. Both the foregoing general description and the following detailed description are merely representative and are intended to provide an overview or framework for understanding the nature and characteristics of the claims. Brief explanation of the drawing The accompanying drawings are included to provide a deeper understanding of this specification, are incorporated into this specification, and constitute part of this specification. The drawings illustrate one or more embodiment(s) and serve to explain the principles and operation of various embodiments together with the description of the invention. FIG. 1 illustrates the volumetric energy density and maximum C-rate capacity as a function of LCO cathode thickness for a LiPON electrolyte (1 μm) and an LLZO electrolyte (20 μm). FIG. 2 is a schematic cross-sectional view illustrating a Li-ion battery having a sintered cathode according to some embodiments. Figure 3 is a schematic cross-sectional view of a conventional Li-ion battery. Figure 4 is a graph of the charging capacity of the battery in Figure 2 compared to the charging capacity of the battery in Figure 3. FIGS. 5 to 8 are scanning electron microscope (SEM) images of polished cross-sections of each sample E1 to E4 according to some embodiments. FIG. 9 illustrates the charging capacity as a function of the charging rate for samples E1 to E4 according to some embodiments. FIG. 10 illustrates the charge capacity at a rate of 1C as a function of perimeter-to-surface area at nominally constant porosity for samples E1 to E4 according to some embodiments. Figure 11 illustrates the capacity modeled at a 1C rate for a 67 μm thick LCO electrode as a function of the concentration of a conductive secondary phase having the conductivity of 1 M LiPF6 in an organic carbonate solution. FIG. 12 illustrates the modeled capacity at a 1C rate for a sintered LCO cathode as a function of the lithium-ion conductivity of the second phase according to some embodiments. Specific details for implementing the invention The following description will be made in great detail regarding representative embodiments illustrated in the accompanying drawings. Where possible, the same reference numerals will be used throughout the drawings to denote identical or similar parts. In the drawings, the scale of the components is not essential; instead, emphasis is given to illustrate the principles of representative embodiments. It should be understood that this application is not limited to the details or methodologies described in the detailed description or illustrated in the drawings. Furthermore, terms should be understood as being for illustrative purposes only and should not be construed as limiting. Additionally, any examples described herein are illustrative but not limiting, and merely describe some of the many possible embodiments of the claimed invention. Other suitable modifications and adaptations of various conditions and parameters commonly encountered in the field and obvious to those skilled in the art are within the spirit and scope of this disclosure. As previously mentioned, current efforts for the development of SS Li-batteries have focused on developing ceramic electrolyte materials with high Li-ion conductivity to minimize internal cell resistance for rapid charging and discharging. Cubic lithium garnet (LLZO), aluminum-doped lithium titanium phosphate (LATP), etc. 10 -4 Having a bulk Li-ion conductivity exceeding S / cm and a thickness of less than 50 μm contributes to an area-specific battery resistance of less than 50 Ω·cm², where area-specific resistance is defined as the thickness of the electrolyte region divided by its lithium-ion conductivity. For comparison, traditionally used lithium phosphorus oxynitride (LiPON) is only 2×10⁻⁶ -6 It has a conductivity of S / cm. The rate of lithium transport in cathode materials tends to be slower than in electrolytes. Table 1 describes the transport parameters for archetype lithium battery cathode materials. cathode material Chemical diffusion coefficient D c (cm² / s) Conductivity (S / cm) ionic, σ Li+ electron's, σ e- Li 1-x CoO2(LCO) a-axis: 2.5X10 -12 Up to 2.5X10 -11 c-axis: 1x10 -13 Up to 6.3X10 -13 a-axis: 1x10 -7 Up to 5X10 -7 c-axis: 5x10 -10 Up to 1.6X10 -7 a-axis: >3.3X10 -2 c-axis: >1X10 -4 That 1-x Mn2O4(LMO) 2X10 -12 to 8X10 -11 1x10 -6 Up to 3x10 -6 1X10 -7 Up to 1X10 -6 LiFePO4(LFP) a-axis: 8x10 -5 b and c axes: 2.2x10 -5 2X10 -5 2X10 -9 The Li-ion conductivity of LCO, LMO, and LFP is much lower than that of ceramic electrolytes such as LLZO and LATP (>10⁻⁴ S / cm). In LCO and LFP, Li-ion conductivity is lower than that of LiPON after factoring in the limitations of slow electron conduction. Among those in Table 1, only LMO is comparable to LiPON in Li-ion conductivity. Therefore, as a result of slow Li-ion conductivity, cathode materials are limited in usable capacity, charging speed, and the ability to deliver sustained power, making the manufacturing of batteries targeting absolute capacity cumbersome and costly. Unbound by theory, the material in the cathode beyond the critical distance from the interface with the electrolyte is inaccessible; that is, the Li-ion conduction rate depends on the critical distance, which itself is a function of the cathode thickness. In other words, the thicker the cathode, the higher the probability that the material in the cathode will move beyond the critical distance from the cathode-electrolyte interface, and thus the Li-ion conduction rate decreases. On the other hand, if the cathode is too thin, inert materials (e.g., the substrate beneath the cathode) can also limit the energy density. Figure 1 illustrates the volumetric energy density and maximum charge rate (C-rate) capability of an LCO cathode as a function of thickness. A similar trend is observed whether the electrolyte is LiPON (1 μm) or LLZO (20 μm): as the cathode thickness increases, the maximum C-rate decreases as the volumetric energy density increases. In the case of the battery structure tested in Fig. 1, the current collectors are copper (Cu) and aluminum (Al) with a thickness of 10 μm each; the total charge transport resistance is the same for both the LiPON electrolyte-containing battery and the LLZO electrolyte-containing battery (20 Ω·cm²); and the maximum C-velocity is estimated from the ohmic current density that produces a potential drop of 1 V. For many electronic devices, a target charging time of at most 1 hour provides ambitious targets for cathode capability and properties. From FIG. 1, to meet this 1-hour charging time requirement, the LCO cathode thickness must be maintained at less than 10 µm, where the capacity of a battery containing a cathode with a thickness of less than 10 µm (e.g., FIG. 3) is less than half of the capacity of the maximum potential for this set of materials (517 mAhr / cm³), because a large portion of the space is dedicated to the inert current collector and electrolyte material. The slow rate of Li transport through the cathode material also increases the manufacturing cost of batteries with absolute capacity targets. The speed of manufacturing processes commonly used to create battery electrodes (e.g., tape casting and calendering) is controlled by the area. The speed of these processes is independent of the electrode thickness. Thicker electrodes are necessary to (i) minimize the number of stacked layers required to build capacity in the battery, (ii) reduce the amount of inert material in the battery, and (iii) reduce capital investment in process equipment. It is expected that the yield will increase as the number of stacked layers in the battery decreases. As described herein, a rapid-sintered (less than 1 hour), self-supported, sintered cathode for a lithium battery is disclosed, wherein the cathode has the following: a thickness optimized to reduce the proportion of inactive components in the battery structure (e.g., as-fired thickness of 10 μm to 200 μm), a second phase of 5% to 35%, and a ratio of active cathode material to the second phase optimized for high storage capacity and high rates of charging and discharging (e.g., 0.4 μm -1The perimeter-to-surface area ratio between the excess active cathode material and the second phase). The perimeter-to-surface area ratio is the total length of the perimeter (P) between the active cathode material (e.g., LCO) and (1) the second phase or (2) the region containing the second phase (e.g., porosity, measured by image analysis of the polished cross-section). T It is defined as ) divided by the total cross-sectional area (A). The active cathode material is lithium cobaltite (LCO); lithium nickel manganese cobaltite (NMC) (e.g., 111-type (Li(NiMnCo) 1 / 3 O2) and 811-type (LiNi 0.8 Mn 0.1 Co 0.1 O2); lithium nickel cobalt aluminate (NCA); lithium iron manganite (LMO), lithium iron phosphate (LFP), or a combination thereof may be included. The second phase may include (1) a porous structure infiltrated with a liquid electrolyte or (2) 10 -4 Solid-state Li-ion conductors having lithium ion conductivity exceeding S / cm (e.g., lithium garnet (LLZO), lithium borate (LBO), perovskite-structured materials (e.g., lithium lanthanum titanate (LTO)), doped lisicon-structured materials (e.g., lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP)), thio-lisicon (e.g., Li 11 AlP2S 12 It may include ), lithium phosphosulfide (LPS), combinations thereof, or doped variations thereof. In some embodiments, the second phase is (3) 10 -10 It may include a mixed conductor having a lithium diffusivity greater than cm² / s (e.g., a solid solution of Nb2O5 and WO3 or other tungstates). The average size of the pores or particles of the second phase may shorten the distance to enable enhanced Li-ion transport in the active cathode material. Referring generally to the drawings, FIG. 3 is a schematic cross-sectional view of a conventional solid-state, thin-film Li-ion battery (100). The battery (100) comprises a cathode current collector (102) and an anode current collector (104) deposited on an inert mechanical support (106). A cathode (108) (e.g., LCO or LMO) is formed on the cathode current collector (102) and surrounded by a solid-state electrolyte (110) (e.g., LiPON). An anode (112) is deposited on the electrolyte (110) and on the anode current collector (104). A coating (114) is provided to protect the cathode (108), the electrolyte (110), and the anode (112). In conventional battery designs, a mechanical support (106) relies on handling during the manufacture of the battery (100) and serves as a platform for the deposition of the cathode (108) and electrolyte (110) layers. The mechanical support (106) typically has a thickness of 50 μm to 100 μm. The mechanical support (106) and the protective coating (114) also help provide rigidity in the final package and prevent damage. In such conventional batteries (100), the cathode (108) is typically grown to a desired thickness by a process such as RF sputtering or pulsed laser deposition. This deposition technique is one reason why conventional batteries (100) require the use of a mechanical support (106). These conventional methods produce cathode material at a rate of <10 μm / hr, which creates practical and commercial limitations on the achievable thickness of these conventional cathode materials. Consequently, thin-film micro-batteries are found only in applications requiring small-sized power sources, such as smart cards, medical implants, RFID tags, and wireless sensing. FIG. 2 is a schematic cross-sectional view illustrating a Li-ion battery having a sintered cathode according to some embodiments. The lithium-ion battery (10) comprises a sintered cathode (12), an electrolyte layer or region (14), and an anode (16). In an embodiment, the sintered cathode (12) has a thickness of 10 μm to 200 μm. Advantageously, the sintered cathode (12) mechanically supports the lithium-ion battery (10) so that the sintered cathode (12) does not advance on an inert mechanical (e.g., zirconia) support. One advantage of this architecture is that the inert component is substantially excluded from the battery structure. That is, while providing the function of a mechanical support, the sintered cathode (12) is still an active component and contributes to the capacity of the battery. Therefore, a cathode-supported design can provide the same total capacity in a thinner form factor (e.g., having a reduced thickness compared to the conventional battery in Fig. 3), or maintain a thickness similar to that of the conventional battery but with a higher net capacity. Additionally, the sintered cathode (12) can be used in both solid-state and liquid electrolyte lithium-ion batteries. In particular, in a solid-state battery, the electrolyte layer (14) comprises a solid-state electrolyte such as LiPON, lithium garnet (e.g., LLZO), lithium phosphosulfide, or lithium superion conductor (LISICON). More specifically, in a solid-state battery, the electrolyte layer (14) has a lithium ion conductivity (e.g., >10 -4Including a solid-state electrolyte having a combination of S / cm) and thickness (e.g., <50 μm), the area-specific resistance is less than about 50 Ω cm². In particular, one advantage of LiPON is that it is resistant to dendrite formation. In a liquid electrolyte battery, the electrolyte layer (14) separates the cathode (12) and the anode (16) by including a liquid electrolyte (e.g., lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bisoxalto borate (LiBOB), lithium difluorooxalto borate (LiDFOB), lithium trifluorosulfonylimide (LiTFSI), or a combination thereof in a carbonate solvent such as ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate (PC), or a mixture thereof) and a polymer or ceramic separator. In any case, the sintered cathode (12) increases the charge capacity compared to a conventional lithium-ion battery. The battery (10) also includes a first current collector (18) disposed on a first surface of a sintered cathode (12). In the illustrated embodiment, a second current collector (20) is disposed on an anode (16); however, in the embodiment, the anode may be a metal (e.g., lithium metal or magnesium metal), in which case the current collector may be omitted. In some embodiments, the sintered anode (16) may comprise at least one of lithium titanate or lithium niobium tungstate. Also, in the illustrated embodiment, the battery (10) is surrounded by a protective coating (22). In the embodiments, the first current collector (18) is copper, and the second current collector (20) (if used) is aluminum. The protective coating (22) may be, for example, parylene. The illustrated embodiment comprises only a sintered cathode (12), but the anode (16) may also be a sintered electrode according to the present disclosure. In the case of a lithium-ion battery, some embodiments of the sintered cathode (12) may comprise at least one of lithium cobaltite, lithium manganite spinel, lithium nickel cobalt aluminate, lithium iron phosphate, lithium cobalt phosphate, lithium nickel manganate, lithium titanium sulfide, or a combination thereof. In some lithium-ion batteries, the cathode (12) may be a rapid-sintered, self-supporting, sintered cathode, said sintered cathode being an active material selected from lithium cobaltite (LCO), lithium nickel manganese cobaltite (NMC), lithium manganite spinel, lithium nickel cobalt aluminate (NCA), lithium iron manganite (LMO), lithium iron phosphate (LFP), lithium cobalt phosphate, lithium nickel manganite, lithium titanium sulfide, or a combination thereof, and (1) a porous structure infiltrated with a liquid electrolyte or (2) 10 -4 Solid-state Li-ion conductors having lithium ion conductivity exceeding S / cm (e.g., lithium garnet (LLZO), lithium borate (LBO), perovskite-structured materials (e.g., lithium lanthanum titanate (LTO)), doped lisicon-structured materials (e.g., lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP)), thio-lisicon (e.g., Li 11 AlP2S 12 It includes a second phase selected from ), lithium phosphosulfide (LPS), combinations thereof, or doped variations thereof. As in (1) of the second phase, the average size of the pores or particles as in (2) can shorten the distance to enhance Li-ion transport in the active cathode material. In some examples, the second phase is (3) 10 -10It may include a mixed conductor having a lithium diffusivity greater than cm² / s (e.g., a solid solution of Nb2O5 and WO3 or other tungstates). Importantly, the sintered cathode (12) has (A) a thickness optimized to reduce the proportion of inactive components in the battery structure (e.g., a sintered-raw thickness of 10 μm to 200 μm), (B) 5% to 25% of a second phase, and (C) a ratio of active cathode material to the second phase optimized for high storage capacity and high-speed charging and discharging (e.g., 0.4 μm -1 It includes at least one of (D) a perimeter-to-surface area ratio between the excess active cathode material and the second phase, and (D) a cross-sectional area of ​​at least 3 cm². The cross-sectional area is defined as the area of ​​the surface in contact with the solid electrolyte separator or porous separator. Additionally, although a lithium-ion battery is depicted, the battery may instead be based on sodium-ion, calcium-ion, or magnesium-ion chemistry. In the case of a sodium-ion battery, the (sintered) cathode (12) is NaMnO2, Na 2 / 3 Mn 1-y Mg y It may include at least one of O2 (0 < y < 1), or NaVPO4F, and the (sintered) anode (16) is Na2Li2Ti5O 12 Alternatively, it may include at least one of Na2Ti3O7. In the case of a magnesium-ion battery, the (sintered) cathode (12) may include at least one of MgCr2O4 or MgMn2O4, and the anode (16) may include magnesium metal (which may also serve as a current collector (20)). Any of the aforementioned battery chemistry may utilize a liquid electrolyte comprising a solvent (e.g., DMC) and a salt having a cation that matches the intercalant ion. Additionally, in the case of a sodium-ion battery, a sodium superionic conductor (NASICON) may be used as a solid-state electrolyte. A comparison of the charging capacity of the battery (10) of FIG. 2 according to the present disclosure and the charging capacity of the conventional battery (100) of FIG. 3 is illustrated in FIG. 4. The comparison is made at a nominally identical thickness of 80 μm. In particular, a comparison is made between (1) a conventional battery (100) having a mechanical support (106) of zirconia with a thickness of 50 μm and a cathode with a thickness of 5 μm, and (2) a currently disclosed battery (10) having a cathode (12) with a thickness of 35 μm. In particular, since the thickness of the cathode (12) of the currently disclosed battery (10) is thinner than the thickness of the mechanical support (106) of the conventional battery (100), it allows space for lithium metal to be secured in the anode (16). As can be seen in FIG. 4, the extra thickness of the sintered cathode (12) and the removal of the mechanical support (106) provide a capacity seven times higher in absolute and volume, and a capacity ten times greater in weight. General description of sintered electrodes and methods for forming the same Various embodiments of the sintered electrode may comprise at least one of an alkali metal, an alkaline earth metal, or a transition metal. The sintered electrode comprises at least one of the following: (A) a thickness optimized to reduce the proportion of inactive components in the battery structure (e.g., a sintered-raw thickness of 10 μm to 200 μm), (B) 5% to 35% of a second phase, and (C) a ratio of active electrode material to the second phase optimized for high storage capacity and high-rate charging and discharging (e.g., 0.4 μm). -1 (D) a perimeter-to-surface area ratio between the excess active electrode material and the second phase, and (D) a cross-sectional area of ​​at least 3 cm². Compared to conventional electrode materials, the sintered electrode can be manufactured to be much larger and self-supporting than typical thin-film formed electrodes, and, in contrast to other sintered electrodes, can be used without additional finishing techniques such as grinding or polishing. The sintered electrodes disclosed herein are designed to be suitable for various battery chemistry, including lithium-ion, sodium-ion, and magnesium-ion batteries, as well as batteries using solid-state or liquid electrolytes. Various embodiments of the sintered electrodes, manufacturing processes, and Li-ion batteries are disclosed herein. These embodiments are provided by way of example rather than by way of limitation. As mentioned, various embodiments of the sintered electrode comprise at least one of an alkali metal (e.g., lithium, sodium, potassium, etc.), an alkaline earth metal (e.g., magnesium, calcium, strontium, etc.), or a transition metal (e.g., cobalt, manganese, nickel, niobium, tantalum, vanadium, titanium, copper, chromium, tungsten, molybdenum, tin, germanium, antimony, bismuth, iron, etc.). In some embodiments, the sintered electrode may comprise oxide, sulfide, selenide, or fluoride compound(s). In some embodiments, the sintered electrode may comprise lithium cobaltite (LCO), lithium nickel manganese cobaltite (NMC), lithium manganite spinel (LMO), lithium nickel cobalt aluminate (NCA), lithium iron manganite (LMO), lithium iron phosphate (LFP), lithium cobalt phosphate, lithium nickel manganate, lithium titanium sulfide (LiTiS2), lithium titanate, lithium niobium tungstate, or a combination thereof. In some embodiments, the sintered electrode may comprise NaVPO4F, NaMnO2, Na 2 / 3 Mn 1-y Mg y O2(0 < y < 1), Na2Li2Ti5O 12 It may include Na2Ti3O7, or a combination thereof. In some embodiments, the sintered electrode may include magnesiochromite (MgCr2O4), MgMn2O4, or a combination thereof. In embodiments, the sintered electrode may comprise multiple phases, such as a second phase, a third phase, a fourth phase, etc., mixed with a first phase. In some embodiments, additional phase(s) are selected to provide additional functions. In one example, for a lithium electrode, a second phase (e.g., lithium garnet) may enhance the effective lithium conductivity of the electrode. In some embodiments, the second phase enhances electronic conductivity. The additional phase(s) may be added prior to sintering, or the sintered electrode may contain open pores that can penetrate into the additional phase(s). In some embodiments, the second phase is spinel, which provides additional electronic conductivity. In some embodiments, the sintered electrode may be manufactured to be larger than a traditional electrode for a battery, such as one manufactured using thin film technology. For example, the thickness of the sintered electrode may be in the range of 10 μm to 200 μm, or 20 μm to 175 μm, or 50 μm to 150 μm, or 75 μm to 125 μm, or 10 μm to 75 μm, or 15 μm to 65 μm, or 20 μm to 50 μm, or 25 μm to 40 μm, or 125 μm to 200 μm, or 140 μm to 180 μm, or 150 μm to 175 μm, or any value or range disclosed herein. In some examples, the sintered electrode may comprise a second phase present in a range of 1% to 50%, or 2% to 40%, or 5% to 35%, or 10% to 30%, or 5% to 40%, or 5% to 30%, or 5% to 25%, or 10% to 40%, or 25% to 40%, or any value or range disclosed herein. In some examples, the sintered electrode is 0.4 μm -1 Exceeding 1 µm, or more. -1 Exceeding 2 µm -1 Exceeding 3 μm -1 Exceeding 4 μm -1 Exceeding or 6 μm -1It may include a perimeter-to-surface area ratio between the active electrode material and the second phase in excess of, or any value or range disclosed herein. In addition to being thicker than thin-film electrodes, sintered electrodes can also be manufactured to have a relatively larger cross-sectional area. In some examples, the sintered electrode is at least 3 cm 2 , or at least 5 cm 2 , or at least 10 cm 2 , or at least 25 cm 2 , or at least 50 cm 2 , or at least 100 cm 2 , or at least 250 cm 2 , or at least 500 cm 2 , or at least 750 cm 2 , or at least 1000 cm 2 , or has a section area of ​​any value or range disclosed therein. In some examples, the sintered electrode is 3 cm 2 up to 25 cm 2 , or 25 cm 2 to 100 cm 2 , or 100 cm 2 up to 500 cm 2 , or 500 cm 2 up to 1000 cm 2 It has a cross-sectional area of ​​a range, or any disclosed value or range. The cross-sectional area is defined as the area of ​​the surface in contact with the solid electrolyte separator or porous separator. The disclosed sintered electrode can achieve these advantages through a tape manufacturing process that allows for a much faster manufacturing speed of "medium" thickness electrode materials, where the process speed is independent of the electrode thickness. That is, the electrode can be manufactured thicker than conventional electrodes manufactured via thin-film technology, and thinner than other sintered electrodes that must be ground to a usable small size. Furthermore, the electrode can be rapidly sintered in a more economical process than currently used to manufacture electrode materials. In fact, conventional processes typically use thin-film technology that is much slower (e.g., at least 15 hours) and more difficult to build thick layers. In this way, the relatively thicker sintered electrode of the present disclosure not only eliminates inert components such as mechanical supports but also increases the charge capacity of the battery. Furthermore, the thickness of the electrode and the tape-casting manufacturing process allow the electrode material to be manufactured in a roll-to-roll format. Since the sintered electrode is formed from a tape cast or extruded green tape in which the electrode is rapidly sintered, it can be manufactured to be larger than conventional thin-film electrodes. To form the green tape, a slurry (or paste) is prepared from a powder component, a binder, and a solvent. The powder component comprises powdered compound(s) comprising at least one of an alkali metal, an alkaline earth metal, or a transition metal. For example, the powder component may comprise at least one of Li2O, Li2CO3, LiOH, LiNO3, lithium acetate (CH3COOLi), lithium citrate (Li3C6H5O7), MnO2, Mn2O3, Co2O3, CoO, NiO, Ni2O3, Fe2O3, Fe3O4, FeO, TiO2, Nb2O5, V2O5, VO2, Ta2O5, WO3, or a combination thereof. In some examples, the powder component of the slurry or paste comprises 40 wt.% to 75 wt.%, or 45 wt.% to 70 wt.%, or 50 wt.% to 65 wt.%, or 40 wt.% to 60 wt.%, or 50 wt.% to 70 wt.%, or any value or range disclosed herein, based on the weight of the slurry (or paste). A binder component of the slurry or paste is provided to hold the powder components together in the form of a green tape prior to sintering. The binder may be at least one of polyvinyl butyral (PVB) (e.g., Butvar® PVB resin, available from Eastman Chemical Company), an acrylic polymer (e.g., Elvacite® acrylic resin, available from Lucite International), or polyvinyl alcohol, or a combination thereof. The slurry (or paste) is also provided with a solvent (e.g., 1-methoxy-2-propanyl acetate (MPA), ethanol-butanol mixture, etc.) in which the powder components and the binder are dispersed. In some examples, the solvent is non-polar and has a dielectric constant of less than 20 at 20°C, or less than 10, or less than 5, or any value or range disclosed herein. In some cases, the chemical properties of the binder can be adjusted to work with non-polar solvents such as MPA. For example, Butvar® B-79 is a commercially available PVB with a low molecular weight compared to other PVB binders, having a low concentration of hydroxyl groups from polyvinyl alcohol (11-13 wt%). This allows for easy dissolution and high solubility to control viscosity and enable high loading of solids. In some examples, the slurry (or paste) may contain other additives to aid the process. For example, the additives may include 0.1% to 5% by weight of a dispersant (e.g., fish-oil dispersant) and / or a plasticizer (e.g., dibutyl phthalate). Other optional additives include antioxidants such as phenols (e.g., butylated hydroxytoluene (BHT) or alkylated-diphenylamine), or endothermic decomposing substances such as inorganic carbonates and hydroxides. The slurry (or paste) is tape-cast or extruded toward a green tape having the desired thickness of the sintered electrode. In an embodiment, the green tape is dried to remove a substantial portion of the solvent, leaving mainly alkali metal, alkaline earth metal and / or transition metal compounds and a binder. Drying occurs at ambient temperature or a slightly elevated temperature of 60°C to 80°C (or starting at ambient temperature and transitioning to the elevated temperature), optionally, under a circulating air environment. The amount of organic material remaining after drying is 10% by weight or less of the dried green tape. During drying, the green tape is de-bound and sintered. De-binding is the green tape being heated to a temperature (e.g., 175°C to 350°C) at which the polymer binder and other organic materials are burned off. Subsequently, the dried and de-bound green tape is continuously sintered. Sintering generally takes place at a temperature range of 500°C to 1350°C for less than 60 minutes, or less than 55 minutes, or less than 50 minutes, or less than 45 minutes, or less than 40 minutes, or less than 35 minutes, or less than 30 minutes, or less than 25 minutes, or less than 20 minutes, or less than 15 minutes, or any value or range disclosed herein. As a result of sintering, in an embodiment, the sintered electrode has a grain size of, on average, 10 nm to 50 μm, 50 nm to 25 μm, 100 nm to 10 μm, 1 μm to 5 μm, or any value or range disclosed herein. In some examples, the sintered electrode has open porosity (wherein the porosity is such that the second phase is a continuous phase from the solid first phase) so that fluid communication is provided between a first surface and another surface of the sintered electrode. Additionally, the pores of the sintered electrode tape can be substantially aligned to promote ion transport, that is, the pores are aligned along an axis perpendicular to the first and second surfaces. For example, each pore may have a cross-sectional dimension longer than any other cross-sectional dimension of the pore, and the longer cross-sectional dimension is aligned substantially perpendicular to the first and second surfaces of the electrode, for example, and is aligned within 25° of the vertical on average. In contrast to other sintered electrodes, the sintering process described herein produces sintered electrodes that do not require additional finishing, such as mechanical grinding or polishing, before being integrated into a battery architecture. In particular, previous sintered electrodes were formed from large discs with much thicker thicknesses, e.g., 500 μm to 1 mm, and had to be diced to usable dimensions and ground to usable thickness. It is reported that such grinding could achieve a thickness of about 130 μm, which is a practical limit for electrodes manufactured according to conventional sintering processes. By tape-casting the electrode as described here, the process is not only more economical (e.g., the absence of grinding / polishing steps and the ability to utilize roll-to-roll manufacturing), but a desired thickness of the electrode material can also be achieved. Examples Example 1 - Tape Casting Process

[0073] Self-supporting LCO cathode ribbons with thicknesses ranging from 45 μm to 85 μm, demonstrating the advantages of a second conductive phase and addressing the problem of slow transport in the cathode material, were prepared by rapid sintering of the tape. The LCO powders for making the tapes were purchased from Shandong Gelon Lib Co., Ltd. (P1) and American Elements (P2), both of which are LiCoO2. Although the composition is nominally identical, the morphology and ultimate particle size of each sample differ. The morphology and particle size were selected as means to manipulate the microstructure beyond the adjustment of sintering conditions. In the received-as-is state, the average particle size of powder P2 is coarser than that of P1, but it can be ground more quickly. For example, the average particle size of P2 particles (0.76 μm) is approximately half that of P1 particles (1.36 μm) after 5 hours of attrition milling in ethanol with a 2 mm diameter milling medium. The formulations of the slip for tape casting (i.e., "slurry"; input into the tape casting process) are shown in Table 2 below. Slip ingredients weight percentage T1 T2 T3 Particle 1 : LCO P1 - - 64.96 Particle 2 : LCO P2 67.04 66.05 - menstruum 1-Methoxy-2-Propanyl Acetate (MPA) 29.98 31.01 32.09 Dispersant Fish Oil 0.59 0.61 0.063 plasticizer : Dibutyl phthalate 0.59 0.61 0.063 bookbinder : Polyvinyl butyral (Butvar B-79) 1.79 1.71 1.69 Total non-volatile organic compounds without MPA 2.97 2.94 2.96 The components of the slip were simultaneously mixed and attrition-milled under equivalent operating conditions. The average particle sizes for P1 and P2 are expected to be consistent with the attrition-milling study performed for 5 hours in ethanol with a 2 mm diameter milling medium, as described above, with approximately 1.36 μm for P1 and approximately 0.76 μm for P2. The slip was cast using a gravity-fed slot die with a width of approximately 50.8 mm. The gate height (i.e., the distance between the top of the gate and the carrier, which defines the space through which the slip flows during tape casting) was set in the range of 8 mil to 12 mil. Casting was performed on a Mylar carrier. A notable feature of these slips and tapes is that the low concentration of non-volatile organic compounds suppresses the flammability of the tape. A strip measured to a length of approximately 200 mm is cut from a roll of dried tape and continuously drawn through a sintering furnace at a speed of 2.5 in / min or 4 in / min. The sintering furnace comprises an 11-inch-long binder burn-out zone (for binder removal) and a 40-mm-long single-pass tube furnace operating at a firing temperature of 1000°C to 1200°C. The organic binder is pyrolyzed by more than 80% by weight at 300°C and nearly completely removed (99%) at 800°C. The total time for this continuous sintering process, including tape heating, soaking, and cooling, is less than 30 minutes in all cases. The soaking time is the time spent at the sintering setpoint temperature. The process properties, properties, and specifications of the rapidly fired LCO ribbon are shown in Table 3 below. Condition or Attribute E1 E2 E3 E4 streamer T1 T1 T2 T3 Firing temperature (°C) 1100 1050 1050 1075 Pull speed (in / min) 4 4 2.5 2.5 Porosity (%) 1.2 20.1 20.5 20.2 Thickness (μm) 47 63 68 81 Perimeter-to-surface area ratio (μm -1 ) 0.32 1.96 1.29 0.93 Example 2 - Attribute Characterization Three discs with a diameter of 12.3 mm were laser-cut from each E1-E4 LCO ribbon (for a total of 12 samples), two of which were evaluated as cathodes in coin cells (8 samples), and one of which was selected for scanning electron microscopy (SEM) analysis (4 samples). The properties of (1) thickness, (2) porosity, and (3) the ratio of the perimeter of the LCO-pore interface to the total cathode structural area were determined by the analysis of high-resolution SEM images of polished cross-sections for E1 to E4, respectively, as shown in FIGS. 5 to 8. Quantifications of (1)-(3) in FIGS. 5 to 8 are provided in Table 3 above. The CR2032 coin cell was assembled with a 14 mm diameter lithium chip as the anode and a 17 mm diameter porous glass fiber filter from Whatman as the separator. The liquid electrolyte was 1 M LiPF6 in a 1:1 mixture of ethylene carbonate and dimethyl carbonate solutions. Three charge-discharge cycles were performed at C-rates of 0.1, 0.3, 0.5, 0.8, and 1, selected based on the theoretical capacity of the LCO being 137 mA·hr / g. Charging was performed under constant current and constant voltage conditions of 3.0 V to 4.3 V. When the current reached a C-rate value of 10%, charging was terminated and discharging was initiated. Constant current conditions were used for discharging. FIG. 9 illustrates the charge capacity as a function of charge rate for samples E1-E4 according to several embodiments. The problem of slow lithium transport in the active cathode material is immediately evident in the capacity of the cell fabricated from the E1 ribbon to the disk. Even at a C-rate of 0.1, the capacity hardly exceeds 20 mA·hr / g, which is less than 15% of the theoretical 137 mA·hr / g. The porosity of the E1 ribbon is low (less than 2%), and the SEM image in FIG. 5 strongly suggests that its pores are completely closed (widely scattered black voids). The liquid electrolyte cannot penetrate the E1 ribbon structure. The capacity of cells fabricated from discs derived from E2-E4 ribbons was dramatically increased by microstructure optimization. These discs all possess a porosity in the range of approximately 20–22%, which allows the pores to open and penetrate the liquid electrolyte. The liquid electrolyte provides a faster path for lithium ion conduction into or out of (i.e., through) the cathode structure. The capacity of cells with the improved E2-E4 ribbon microstructure charged at a C-rate of 0.1 is seven times higher than that of cells with LCO derived from E1 ribbons, with the range being 150 mA·hr / g to 160 mA·hr / g. It is noted that charging at 4.3 V induces a capacity several percent higher than theoretically. Furthermore, E2-E4 is thicker than E1. The areal capacity of an electrode increases with its thickness, and consequently, a proportionally higher current density is required to charge at a given C-rate. The thickness of E2-E4 was designed to limit this effect. E1 exemplifies the need for a second phase; despite being thinner than E2-E4, the E1 capacity is lower at all C-velocities. Therefore, in some embodiments, the amount of the second phase is more important than the cathode thickness. The capacity for filling an LCO disk containing an E2-E4 ribbon exhibits a strong trend toward the microstructure as the filling rate increases. FIG. 10 illustrates the filling capacity at a 1C rate as a function of the perimeter-to-surface area ratio at a nominally constant porosity for a sample E2-E4 according to some embodiments. Specifically, the capacity at a 1C rate is quantified as a function of the ratio of the perimeter length between the active LCO and the pore to the total area of ​​the cathode structure. The perimeter-to-surface area ratio is the total length of the perimeter (P) between the active cathode material (e.g., LCO) and (1) the second phase or (2) the region containing the second phase. TIt is defined as dividing porosity (e.g., measured by image analysis of a polished cross-section) by the total cross-sectional area (A). The perimeter-to-surface area ratio is a surrogate for the surface-to-volume ratio and is directly proportional to the surface-to-volume ratio. Therefore, any trends observed for the perimeter-to-surface area ratio can be equally applied to the surface-to-volume ratio. The tendency for capacity to increase with a higher perimeter-to-surface area ratio (likewise for a higher surface-to-volume ratio) may be because the local distance for the transport of lithium ions into and out of the active cathode material decreases as the surface-to-volume ratio increases relative to a fixed porosity. As the surface-to-volume ratio increases, there is a larger area for charge transport reactions at the cathode. The E2 ribbon, which has the highest perimeter-to-surface area ratio among E1-E4, also exhibits the highest capacity in Figure 10, so the theory is confirmed by the data. The microstructure of E2-E4 not only has an optimal amount of the second phase of approximately 10-25% but also 0.4 μm -1It has a larger and higher surface-to-volume (perimeter-to-surface area) ratio. Figure 11 illustrates the capacity modeled at a 1C rate for a 67 μm thick LCO electrode as a function of the concentration of a conductive secondary phase (e.g., when the conductive secondary phase is porous) having the conductivity of 1 M LiPF6 in an organic carbonate solution. Values ​​for the model parameters for the components containing LCO were collected from the scientific literature. The capacity was calculated for a 67 μm thick cathode structure with two pore diameters, 1 μm and 3 μm, at a 1C rate under the same constant current and constant voltage conditions as described above. As porosity is introduced into the cathode, the available capacity during charging increases rapidly; the local distance for lithium transport through the LCO is shortened, and the area for charge transport increases. The available capacity decreases after reaching a peak, because after the tipping point concentration of porosity, adding more porosity only serves to reduce the amount of LCO in the cathode structure beyond the critical threshold value. The optimal volume percentage of the secondary conductive liquid phase is approximately 10 to 25%, which is highlighted in gray in Fig. 11. The capacity is greatest in this highlighted area and changes relatively slowly as a function of the volume percentage of the second phase. Furthermore, the capacity in the highlighted area is ideal for the process of controlling battery performance and microstructure. Fig. 11 also demonstrates the beneficial effect of increasing the surface-to-volume ratio by reducing the pore size or, alternatively, the area of ​​the secondary lithium-ion conductive phase. As experimentally demonstrated above for samples E1-E4, the model confirms that the charge capacity is greater in the case of a higher surface-to-volume ratio. Figure 11 models the case where the conductive secondary phase is porous, and this approach can be extended to include a solid lithium-ion conductive secondary phase for all solid-state batteries. Figure 12 illustrates the modeled capacity at a 1C rate for a sintered LCO cathode as a function of the lithium-ion conductivity of the second phase. Specifically, the charge capacity at a 1C rate was modeled for a 67 μm thick LCO cathode having 15 volume% of a secondary phase lithium-ion conductor as a function of the lithium-ion conductivity of the second phase. The secondary lithium-ion conductor has a conductivity of approximately 10 -4 When rising above S / cm, rapid transport of lithium can be enabled through the cathode structure. In the above examples, the optimal microstructure was achieved by adjusting the particle size, particle packing, and sintering conditions. Further improvements in the microstructure can be achieved according to FIG. 11 by using cathode particles of finer size by grinding for a longer time, or by using cathode material from a process such as flame pyrolysis that is naturally small (e.g., less than 300 nm), or by increasing the surface-to-volume ratio. One problem in developing a structure such as that disclosed herein is maintaining the continuity of the second phase below a specific critical concentration value. One way to solve this problem may be to ensure that the average particle size of the solid secondary lithium-ion conductive phase is smaller than the average particle size of the active cathode material. Smaller secondary particles tend to accumulate in the interstices between cathode particles, which can connect and form a continuous network. The particle size of the cathode material can also be utilized to maintain the continuity of porosity for penetration by liquids. A significant proportion of fine particles (e.g., d 10A particle size distribution with < 200 nm is advantageous because it can increase packing density, and because fine components sinter and bond larger particles together while maintaining a continuous pore network. The disclosed electrode is advantageous to the performance of all solid-state batteries and to the process of manufacturing it in the following ways: (A) the ratio of the active cathode material to the second phase is optimized to provide both 1C and high storage capacity for high rates of charging and discharging in a cathode structure having a thickness greater than 20 μm; (B) the defined average size of the pores or particles of the second phase shortens the distance for lithium transport in the active cathode material; (C) the internal surface area between the electrolyte and the active cathode material is increased compared to a flat electrode-electrolyte interface, thereby reducing the contribution of charge transport to the total cell resistance; and (D) the thicker cathode structure reduces the proportion of inactive components in the battery, and the cathode can also function as a free-standing substrate for the deposition of thin solid electrolytes (e.g., LLZO or LiPON) to a thickness of 10 μm or less via thin film deposition, spray coating, and casting; (E) The absolute capacity target for the battery can be achieved with a smaller cell area, i.e., in pouch or cylindrical cells, with fewer layers or windings, respectively; (F) the thicker cathode is structurally less brittle and is easier to fabricate, handle, and assemble into a battery; and (G) as described above, a rapid, continuous sintering process for co-firing the active cathode material and the lithium-ion conductive second phase is provided, resulting in fewer unwanted reactions. Specifically, in (D), since the sintered electrode is self-supporting, the sintered electrode can be used as a substrate for the deposition of additional layers. For example, a metal layer (e.g., up to 15 μm) can be deposited on the surface of the sintered electrode to serve as a current collector for the battery. Additionally, in some examples, lithium-phosphorus-oxynitride (LiPON), lithium garnet (e.g., garnet LLZO (Li7La3Zr2O2)) 12 Solid electrolytes such as )), or lithium phosphate sulfide, can be deposited on sintered electrodes by RF-sputtering. Alternatively, a thin layer of LiPON solid electrolyte can be applied via ammonolysis of a thin layer of Li3PO4 or LiPO3 or via reactive sintering. These processes are considered to be faster and potentially less capital-intensive than conventional deposition techniques for solid electrolytes. Similarly, solid electrolytes of lithium garnet (e.g., LLZO) can be applied by sol-gel, direct sintering, and reactive sintering. Furthermore, as a self-supporting layer, the sintered electrode can provide the basis for an advantageous manufacturing approach for lithium batteries using liquid electrolytes. In other words, the cathode (i.e., the sintered electrode) is the substrate of the battery. In particular, the sintered electrode can be manufactured in a continuous process and can be used as a substrate for coating in a batch or roll-to-roll process. These processes allow for the metallization of the sintered electrode, for example, by sputtering and / or electrolytic deposition, thereby forming a metallized sintered electrode. In this way, the thickness of the metal can of the electrode current collector for conventional lithium batteries can be reduced from a typical thickness of 10–15 µm to less than 5 µm, less than 1 µm, or even less than 100 nm. Additionally, the metallized sintered electrode can be supplied to battery cell manufacturers in the form of pieces or rolls as standalone components. Advantageously, these metallized sintered electrodes reduce the cell volume typically reserved for the current collector, allowing for more active electrode material and higher capacity. In addition to simply allowing for a larger electrode, the disclosed sintered cathode (12) also provides a structural advantage that increases charge capacity compared to conventional cathodes. In the calendered cathode (108), the active cathode particles make point contacts. Because the cross-sectional area of ​​the contact is small, it has a high impedance for the movement of lithium ions and electrons. To overcome this impedance problem, carbon is added to the electrode as a conductive path that facilitates the transport of electrons into and out of the active particles. In this way, the use of carbon creates a tradeoff between battery capacity and charge / charge rate performance. Another problem associated with the point contacts between the active cathode particles is that, because they are weak, polyvinyl fluoride (PVF) is used to bond the active particles and carbon together, thereby providing structural strength during the process. In contrast, the particles of the illustrated sintered cathode (12) are bonded together, and thus the electronically conductive carbon and binder can be removed after sintering. In this way, the proportion of space allocated to porosity for the movement of lithium ions can be reduced, and more space can be allocated to the active material having the sintered cathode. The inventors estimate that for a given cathode material, the total capacity can be increased by approximately 30% relative to the same cathode thickness. Alternatively, the cathode thickness can be reduced by 20-25% while maintaining the same capacity for a more compact battery. As described above, the pores in the sintered cathode (12) can be aligned toward and from the anode in the direction of ion transport to enable further improvement in space utilization or to increase power density. As used herein, the term “porosity” is described in volume percentage (e.g., at least 10 volume%, or at least 30 volume%), where “porosity” refers to the portion of the volume of the sintered article not occupied by inorganic material. Unless otherwise explicitly stated, any method described herein is not intended to be interpreted as requiring its steps to be performed in a specific order. Accordingly, the method claim is not intended to be presumed to be in any specific order unless the order of the steps is not substantially enumerated, or unless specifically stated in the claim or detailed description that the steps are limited to a particular order. As used herein, the terms “approximately,” “about,” “substantially,” and similar terms are intended to have a broad meaning in harmony with the general and acceptable usage by those skilled in the art relating to the subject matter of this disclosure. Those skilled in the art reviewing this disclosure should understand that these terms are intended to allow for the description of the specific features described and claimed without limiting the scope of these features to the precise numerical ranges provided. Accordingly, these terms should be interpreted to indicate that any minor or insignificant modification or alteration of the subject matter described and claimed is deemed to be within the scope of the invention as described in the appended claims. As used herein, terms such as "optional," "optionally," etc., are intended to mean that an event or situation described below may or may not occur, and that the description includes cases where the event or situation occurs and cases where it does not occur. As used herein, the singular of terms means at least one or more than one, unless otherwise noted. References herein to the position of an element (e.g., "top," "bottom," "up," "down," etc.) are used merely to describe the orientation of various components in the drawings. It should be noted that the orientation of various components may vary according to other exemplary embodiments, and such changes are intended to be included by the present disclosure. With regard to the use of any plural and / or singular term substantially herein, a person of ordinary skill may translate from plural to singular and / or singular to plural as appropriate to the context and / or application. Various singular / plural permutations may be explicitly described herein for clarity. It will be obvious to a person skilled in the art that various modifications and changes can be made without departing from the spirit or scope of the disclosed embodiments. Because variations, combinations, sub-combinations, and changes of the disclosed embodiments incorporating the spirit and materials of the embodiments may occur to a person skilled in the art, the disclosed embodiments should be interpreted as including everything within the scope of the appended claims and their equivalents.

Claims

Claim 1 A sintered electrode for a battery, wherein the sintered electrode has a first surface positioned toward a current collector and a second surface positioned toward an electrolyte layer, wherein the sintered electrode comprises: a first phase and a second phase, wherein: the first phase comprises a lithium compound, and the second phase comprises a solid-state Li-ion conductor present in a range of 5% to 35% based on the volume of the sintered electrode, and the thickness of the sintered electrode between the first surface and the second surface is in the range of 10 μm to 200 μm, and the solid-state Li-ion conductor comprises: lithium borate (LBO), Li 11 AlP2S 12 A sintered electrode comprising at least one of lithium phosphosulfide (LPS), a combination thereof, or a doped variant thereof, wherein the lithium compound comprises lithium cobaltite (LCO). Claim 2 In claim 1, the solid-state Li-ion conductor is 10 -4 Sintered electrode having lithium ion conductivity exceeding S / cm. Claim 3 In claim 1, the perimeter-to-surface area ratio between the first phase and the second phase is at least 0.4 μm -1 Phosphorus, sintered electrode. Claim 4 delete Claim 5 delete Claim 6 A sintered electrode according to any one of claims 1 to 3, wherein the sintered electrode further comprises a porous structure continuous with a first phase, and the second phase is located within the porous structure. Claim 7 delete Claim 8 A battery comprising a sintered electrode according to any one of claims 1 to 3, wherein the sintered electrode is a self-supporting substrate of the battery. Claim 9 A battery comprising a sintered electrode according to any one of claims 1 to 3, wherein the battery does not comprise an inert substrate. Claim 10 delete Claim 11 delete Claim 12 delete Claim 13 delete Claim 14 delete Claim 15 delete Claim 16 delete Claim 17 delete Claim 18 delete Claim 19 delete

Citation Information

Patent Citations

  • Electrode composite body, method of manufacturing electrode composite body, and lithium battery

    CN106252590A

  • Lithium secondary battery

    JP2013012338A

  • Lithium secondary battery and method for producing same

    US20060003226A1

  • Impregnated sintered solid state composite electrode, solid state battery, and methods of preparation

    US20150056520A1

  • Lithium composite oxide sintered body plate and lithium secondary battery

    WO2018147248A1